Descriptions of the larvae and pupae of Sisko Ross with notes on western Dolophilodes Ulmer larvae (Trichoptera: Philopotamidae) - Lee, Jonathan (Zootaxa, 2024)
Larvae and a pupa of the caddisfly genus Sisko Ross (Trichoptera: Philopotamidae) are described. Larval and pupal photos and larval diagnoses are provided. Larval head and mandible photos and notes are provided for four species of western Dolophilodes Ulmer. A key to the larvae of North American Philopotamidae genera is included.